Kajian Etnobiologi Terites dan Kidu-Kidu Makanan Budaya Suku Batak Karo di Sumatera Utara - Ashar Hasairin; Aswarina Nasution (The Ethnobiological Society of Indonesia, 2021)
The Karo Batak tribe has traditional knowledge about food technology which is very unique and almost not found in other ethnic groups in North Sumatra. This study aims to examine the ethnobiology of the typical traditional Batak Karo food, namely terites and kidu-kidu. This research was conducted in Berastagi and Kabanjahe, Karo District. The exploratory survey research method used interview techniques to traditional leaders and local communities. The results showed that the raw material for traditional food terites was squeezed for ruminant animal food, which had not yet passed through the small intestine. Meanwhile, kidu (Rhynchophorus ferruginemis) is obtained or taken from the palm tree. Every food has a ritual meaning for the Karo ethnic and cannot be separated from their life. This food is mixed with various herbs and spices which are closely related to the natural resources around it. Terites uses nine types of spices and kidu-kidu uses seven types of spices. The typical use of spices from the bark of the cingkam tree (Bischofia javanica) has a high enough tannin content.